Evaluating effectiveness of an integrated return-to-work and vocational rehabilitation program on work disability duration in the construction sector - Robert A Macpherson; Ailin He; Benjamin C Amick III; Mieke Koehoorn; Christopher B McLeod (Nordic Association of Occupational Safety and Health (NOROSH), 2022)
OBJECTIVE: The aim of this study was to investigate whether an integrated return-to-work (RTW) and vocational rehabilitation (VR) program - the Work Reintegration (WR) program - was associated with reduced work disability duration in the construction sector in Ontario, Canada. METHODS: Workers' compensation data from the Ontario Workplace Safety and Insurance Board were extracted for lost-time construction worker claims following work-related injuries between 2009 and 2015. Claims receiving referrals to RTW and VR specialists (treatments) were matched with claims receiving no referrals (controls) during the periods before and after the WR program introduction. Multivariable difference-in-differences linear and quantile regression models were used to examine differences in cumulative disability days paid during two-years post-injury between treatment and control groups before and after the program change and the difference in these differences, overall, and at different disability distribution percentiles. RESULTS: The WR program introduction was associated with reductions in cumulative disability days paid for all claims but most notably among longer duration claims referred to RTW specialists (reduction of 274 days at the 90^th percentile in the disability distribution) and shorter duration claims referred to VR specialists (reductions of 255 and 214 days at the 25^th and 50^th percentiles in the disability distribution, respectively). CONCLUSIONS: The WR program introduction was effective in reducing cumulative disability days paid for construction worker claims but the effects varied at different percentiles in the disability distribution, as well as by specialist referral. The findings highlight the benefits of better integrated RTW and VR services to injured workers in the construction sector.